“How we do it”: A qualitative study of strategies for adopting an exercise routine while living with type 1 diabetes - Vlcek, Cristine; Greenberg, Dana; Yardley, Jane E.; Klaprat, Nika; MacIntosh, Andrea; Greenberg, Marley; Brandt, Joel; Gregoire, Natasha; Dostie, Sylvie; Boutin, Denis; Pow, Conrad; Archibald, Mandy; et al. (Frontiers in Endocrinology, 2023)
Introduction: For people living with type 1 diabetes (T1D) the challenge of increasing daily physical activity (PA) is compounded by the increased risks of hypoglycemia and glucose variability. Little information exists on the lived experience of overcoming these barriers and adopting and maintaining an active lifestyle while living with T1D. Research Design and Methods: We conducted a patient-led qualitative study consisting of semi-structured interviews or focus groups with 22 individuals at least 16 years old living with T1D. We used existing patient co-researcher networks and snowball sampling to obtain a sample of individuals who reported being regularly physically active and had been diagnosed with T1D for at least one year. We used an interpretive description analysis to generate themes and strategies associated with maintaining an active lifestyle while living with T1D. We involved patient co-researchers in study design, data collection, and interpretation. Results: 14 self-identified women and 8 self-identified men (ages 19-62, median age 32 years) completed the study, led by either a researcher, or a patient co-researcher and research assistant regarding their strategies for maintaining an active lifestyle. We identified five themes that facilitate regular sustained PA: (1) Structure and organization are important to adopt safe PA in daily life “I can't do spontaneous exercise. I actually need a couple hours of warning minimum”; (2) Trial and error to learn how their body responds to PA and food “Once you put the time and effort into learning, you will have greater success”; (3) Psychosocial aspects of PA “…because it's not just your body, it's your soul, it's your mind that exercise is for”; (4) Diabetes technology and (5) Education and peer support.. Strategies to overcome barriers included (1) Technology; (2) Integrating psychosocial facilitators; (3) Insulin and carbohydrate adjustments; and (4) Planning for exercise. Conclusions: Living an active lifestyle with T1D is facilitated by dedicated structure and organization of routines, accepting the need for trial and error to understand the personalized glycemic responses to PA and careful use of food to prevent hypoglycemia. These themes could inform clinical practice guidelines or future trials that include PA interventions.